Solution Heat Treatment of the Single Crystal Nickel‐Base Superalloy CMSX‐4 Fabricated by Selective Electron Beam Melting1. Issue 10 (3rd April 2015) - Ramsperger, Markus; Mújica Roncery, Laís; Lopez‐Galilea, Inmaculada; Singer, Robert F.; Theisen, Werner; Körner, Carolin
<x xml:space="preserve">Abstract</x> Selective electron beam melting (SEBM), which belongs to the additive manufacturing processes, is applied to produce samples from the single crystalline nickel‐base superalloy CMSX‐4. The influence of the high solidification rates on the microstructure and element distribution is investigated by OM, SEM, DSC, and EMPA. Solution heat treatments at different temperatures and holding times are applied to demonstrate the difference between conventionally cast and SEBM material. The results demonstrate that SEBM is able to produce superalloys with a degree of homogeneity which cannot be realized in conventional processes.